Peningkatan Kemampuan Berpikir Kritis Mahasiswa pada Media melalui Film dan Model Discovery Learning - Muh. Bahruddin (Universitas Negeri Medan, 2020)
This study aims to determine the increase in critical thinking skills of Visual Communication Design studens at Universitas Dinamika in the mass media. This research focuses on the ability to identify, discover, and solve problems. Researcher used a film medium called